ANALISIS DAMPAK PENGEMBANGAN KARIR, DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP PRODUKTIVITAS KARYAWAN PG. MKBN - Azifah, Niswatul; Hidayati, Roziana Ainul (Kinerja, 2022)
PG. MKBN is one of the sugar factories with the largest capacity in Indonesia. With labor-intensive systematics, employee productivity is an important thing to improve in order to achieve goals and targets. But in reality, the productivity of PG. MKBN employees has decreased over the last 4 years. This research focuses on career development factors and perceived organizational support which are unresolved problems. This research was conducted in PG. MKBN with the aim of knowing the influence, impact, and to what extent it is caused by career development factors and perceived organizational support causing decreased employee productivity, as well as finding solutions for settlement. This research uses a descriptive method with a qualitative approach. The data collection technique used was interview, documentation, and observation with the Head of HR & General PG. MKBN, Employees of HR & General Managers, Permanent Executive Employees 1, and Permanent Executive Employees 2. The results of the data analysis showed that the two factors, namely career development and perceived organizational support , were very influential and had an impact on the level of employee productivity at PG. MKBN. Employees who feel that the implemented career development is not optimal, and have a low level of perceived organizational support will have an impact on reducing employee motivation which causes targets not to be achieved, high levels of indiscipline, difficulty in innovating, and work cycles that do not care about the quality of output which has an impact on the decline in employee productivity at PG. MKBN.